Local prestressing of cold forging tools by reinforcements with adapted interference - Killmann, Martin; Merklein, Marion (Procedia Structural Integrity, 2022)
With contact pressures of more than 3000 MPa cold forging dies belong to the highest loaded components in mechanical engineering. Especially in non-symmetrical dies, this leads to a complex stress state with locally varying stresses. Cyclically occurring tensile stress concentrations cause crack initiation, which is why fatigue is the most important failure mechanism for complex cold forging tools. To reduce tensile stresses and counteract fatigue failure, dies are conventionally prestressed by inserting them into a reinforcement ring with a uniformly distributed interference. However, the compressive prestress is often not enough to compensate the high local stresses occurring in processes for non-symmetrical parts. Therefore, this paper focuses on using a non-uniformly distributed interference to locally increase prestresses in critical areas. To achieve this, gaps are inserted between die and reinforcement, inducing a bending stress. A numerical model is used to analyse how to design the gaps depending on the interference fit and how effective the use of gaps is for different part geometries with an increasing number of functional elements. Results show, that gap angles between 40° and 60° are suitable for locally improving the stress state. For high interferences, too large gap angles increase tensile stresses occurring in other areas of the dies, possibly impeding tool life. Since the adapted interferences work based on a bending effect, gaps are effective for up to four uniformly distributed critical areas. For more local elements, the lever distance is too low to apply an effective bending stress and the stress state does not improve. <
Keywords: Cold forging; Die design; Tool life; Local prestressing